Assistance in BIPA Learning Management and Institutional Internationalization at Al Irtiqo' International Islamic Senior High School Malang - F. Faizin; M. Isnaini (Direktorat Penelitian dan Pengabdian Kepada Masyarakat, 2021)
The teaching assistance activity of BIPA Al Irtiqo’ International Islamic Senior High School Malang, aims to build cooperative relations between institutions and develop science in the fields of education, Indonesian language and culture and in a broad scope as Indonesian cultural diplomacy. Moreover, this is a form of special services for the increasing exchange of students to schools with various schools from abroad. Therefore, it is considered very important to provide basic provisions for teaching strategies and management of BIPA learning in schools as well as internationalization of institutions that have foreign cooperation partners. Language learning emphasizes listening, speaking, reading and writing skills. Meanwhile, internationalization is manifested through guidelines and mechanisms of cooperation between institutions